Polymorphism of Janus Kinase 2 and Telomerase Reverse Transcriptase Genes in Iraqi Patients with Myeloproliferative Neoplasm - Nasif, Zaizafoon N.; Muftin, Najlaa Qassim; Hameed, Aseel M.; Yasir, Luma A. (Iraqi Journal of Science, 2025)
Specific somatic mutations in any of the three genes—JAK2, CALR, or MPL—are frequently found in myeloproliferative neoplasms (MPNs), which include polycythaemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (PMF). The rs2736100 in the telomerase reverse transcriptase gene (TERT) increases the risk of MPN disease in Iraqi subjects. This research attempted to investigate the prevalence of TERT rs2736100 and JAK2V617F in Iraqi patients with MPN and normal population. According to the collected data, significant correlation was indicated between the allele T of TERT rs2736100 and the prevalence of MPN (OR =3.3108, 95% CI =1.3828 to 7.9269, P =0.0072). Additionally, we have observed that the allele T of TERT rs2736100 has been correlated significantly with JAK2 V617F-positive MPN (OR = 4.0737, 95% CI (1.8347 to 10.8681) P = 0.0010). In accordance, the present work revealed a link between the TERT gene polymorphism rs2736100 and the development of MPN in an Iraqi population sample. Hence, it can be stated that the TERT rs2736100 polymorphism has a key impact over the development of MPN. Nevertheless, more investigations should be proceeded on larger population to validate this outcome.